Bioactive Potentials of Cleome viscosa L. Extracts: Dose-mortality, Insect Repellency and Brine Shrimp Lethality (Journal of Scientific Research, 2017)
Petroleum ether (Pet. ether), chloroform (CHCl3) and methanol (CH3OH) extracts of Cleome viscosa have thoroughly screened against Tribolium castaneum (Hbst.) for repellency and dose mortality, against Callosobruchus chinensis for dose mortality activities, and against Artemia salina nauplii for lethality. In case of repellency of T. castaneum, Pet. ether extract found significantly active at 1% level of significance (P < 0.01), CHCl3 extract offered activity at 5% level of significance (P < 0.05) and CH3OH extract did not show any activity at all. In case of mortality against T. castaneum  the LD50 values of Pet. ether, CHCl3, and CH3OH extracts were 2.380, 2.188, 1.867, 1.658 and 1.429 mg/cm2; 4.950, 2.906, 2.664, 2.658 and 2.609 mg/cm2; and 4.950 and 2.791, 2.609, 2.552 and 2.474 mg/cm2 after 0.5, 6, 12, 18 and 24 h of exposure respectively.  Against C. chinensis the LD50 values of the same extracts were 0.781, 0.670, 0.642, 0.614, 0.560 and 0.494 mg/cm2; 1.964, 1.050, 0.867, 0.725, 0.635 and 0.590 mg/cm2; and 2.631, 1.851, 1.471, 1.703, 1.524 and 1.457 mg/cm2 after  6, 12, 18, 24, 30 and 36 h of exposure respectively. In case of cytotoxicity test against A. salina, the extracts offered LC50 values in a descending order CH3OH > CHCl3 > Pet. ether extracts.